Acneiform eruptions in dermatology : a differential diagnosis - Albahrani, Yasser; Alexis, Andrew F.; Baldwin, Hilary; Ballin, Annelyse; Bernardo, Sebastian; Zeichner, Joshua A. (New York : Springer, 2014)
Dermatologists commonly treat acne, which affects 40 to 50 million Americans each year and about 85 percent of all patients at some point in their lives. Dermatologists, primary care doctors, and pediatricians see these patients every day in practice. It is important to treat the skin effectively not only to reduce the risk of physical scarring, but also to address the negative psychosocial impact this disease carries. Improving the skin can improve self-confidence, interpersonal relationships, and performance in school or at work. Acneiform Eruptions in Dermatology is a practical, full-color guide to the differential diagnosis of acne vulgaris and the treatment of acne-like conditions. It is organized into sections by subtype of condition (e.g., infections, genetic syndromes, medication-caused) and includes a section of variants of acne that may be misdiagnosed. Within the sections, individual chapters discuss each variant of the condition and beginwith a helpful bulleted summary of its defining clinical features. Extensive color clinical images appear throughout the book.
La función de los autores fue determinada por el catalogador
Keywords: ACNE -- DIAGNOSTICO; ACNE -- TRATAMIENTO